2004
DOI: 10.1128/jvi.78.15.7958-7968.2004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Hepatitis C Virus Core Protein to Mitochondria through a Novel C-Terminal Localization Motif

Abstract: The hepatitis C virus (HCV) core protein represents the first 191 amino acids of the viral precursor polyprotein and is cotranslationally inserted into the membrane of the endoplasmic reticulum (ER). Processing at position 179 by a recently identified intramembrane signal peptide peptidase leads to the generation and potential cytosolic release of a 179-amino-acid matured form of the core protein. Using confocal microscopy, we observed that a fraction of the mature core protein colocalized with mitochondrial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
144
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(157 citation statements)
references
References 74 publications
9
144
1
2
Order By: Relevance
“…The core protein showed a partial co-localization with Cardif in mitochondria in the UCp7con-9 cell line. Previous studies have shown that the core protein is located in lipid storage vesicles (Barba et al, 1997) and also in the outer membrane of mitochondria (Schwer et al, 2004). In the UHCV-11 cell line, the staining for NS3 was weaker compared with that seen in UNS3-4A-24 cells.…”
mentioning
confidence: 72%
“…The core protein showed a partial co-localization with Cardif in mitochondria in the UCp7con-9 cell line. Previous studies have shown that the core protein is located in lipid storage vesicles (Barba et al, 1997) and also in the outer membrane of mitochondria (Schwer et al, 2004). In the UHCV-11 cell line, the staining for NS3 was weaker compared with that seen in UNS3-4A-24 cells.…”
mentioning
confidence: 72%
“…Mitochondria were purified using Nycodenz (Nycomed Pharma, Zürich, Switzerland) according to the protocols reported by Okado-Matsumoto et al 17 For transient transfection experiments, HepG2 cells were transfected with a core-expression plasmid using TransIT-LT1 (Mirus Bio, Madison, WI). Huh7 cells harboring HCV genotype 1b full-genomic (RCYM1) 18 or subgenomic replicon (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and livers of 3-month-old core-gene transgenic mice 2 were also used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…2,5,6 In addition, the double structure of mitochondrial membranes is disrupted in hepatocytes of core-gene transgenic mice. [2][3][4] Evidence suggests that the core protein modulates some mitochondrial functions, including fatty acid ␤-oxidation, the impairment of which may induce lipid abnormalities and hepatic steatosis.…”
mentioning
confidence: 99%
“…Although numerous proteins localize to both the ER and the mitochondria (bcl-2, cytochrome), sequential trafficking of proteins from the ER to mitochondria has been rarely found (12,27,41). More often, the case is that separate but competitive trafficking of proteins occurs into either secretory apparatus or mitochondria (16,22,39).…”
Section: Vol 82 2008 Hcmv Pul37x1 Traffics Through the Mam 2721mentioning
confidence: 99%
“…Because this protein is anchored in the membrane by three transmem-brane domains, we hypothesized its sequential trafficking from ER to mitochondria occurs through a continuous lipid bilayer connecting the two organelles. Although localization of proteins in the ER and in mitochondria is frequently observed (3,9,23), few cellular (12) and viral (27,41) proteins are known to traffic sequentially from the ER to mitochondria. Consequently, this trafficking pathway connecting the ER to mitochondria is poorly understood.…”
mentioning
confidence: 99%